Timing of magmatism and mineralisation at Falun, a major base metal sulphide deposit in the Fennoscandian Shield, Sweden - Kampmann, Tobias; Stephens, Michael B.; Ripa, Magnus; Hellström, Fredrik (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2015)
U-Pb (zircon) ion probe geochronology on key lithologies at the Palaeoproterozoic Falun Zn-Pb-Cu-(Au-Ag) sulphide deposit in the south-western part of the Fennoscandian Shield has been carried out. Results suggest that dominantly felsic sub-volcanic intrusion, hydrothermal alteration, ore formation and intrusion by dykes and plutons took place in a short time interval between 1894 ± 3 Ma and 1891 ± 3 Ma. Analogues to intra-arc VMS mineralisation in Peru are discussed. Godkänd; 2015; 20150831 (tobkam) Structural evolution, hydrothermal alteration and tectonic setting of the Falun base metal and gold deposit, Bergslagen region, Sweden